2005
DOI: 10.1093/mutage/gei021
|View full text |Cite
|
Sign up to set email alerts
|

The genotoxic effects of hepatitis B virus to host DNA

Abstract: Chronic viral hepatitis is the main cause of chronic liver disease, cirrhosis and hepatocellular carcinoma throughout the world. Hepatitis B virus (HBV) has mutagenic effects on somatic cells. HBV may be showing these mutagenic effects through its viral proteins or through integrating into host DNA. The aim of this study was to determine whether HBV has a genotoxic effect on host DNA or not. Peripheral blood lymphocytes of 31 chronic HBV patients and 20 chronic HBV carriers were cultured in order to make cytog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…In the present study, we demonstrated that the lymphocytes of HBV-infected patients and HCV-infected patients exhibited an increased frequency of MN compared with lymphocytes from healthy, non-infected individuals. This result is in contrast to findings previously reported by Ozkal et al (2005) . However, these authors reported a higher frequency of chromosome breaks, leading to the formation of acentric chromosome/chromatid fragments that ultimately contributed to the formation of MN.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, we demonstrated that the lymphocytes of HBV-infected patients and HCV-infected patients exhibited an increased frequency of MN compared with lymphocytes from healthy, non-infected individuals. This result is in contrast to findings previously reported by Ozkal et al (2005) . However, these authors reported a higher frequency of chromosome breaks, leading to the formation of acentric chromosome/chromatid fragments that ultimately contributed to the formation of MN.…”
Section: Discussioncontrasting
confidence: 99%
“…The presence of ALS in the genome appears to be a structural feature of chromatin. The induction of chromatin changes is an emerging topic in the study of viral tumorigenesis in humans, not only in relation to high-risk HPV types 20 but also to hepatitis B virus, 21 Kaposi's sarcoma herpesvirus, 22 and human T-cell leukemia virus type 1 (HTLV-1). 23 …”
Section: Results and Dicussionmentioning
confidence: 99%
“…There is increasing evidence that HBV infection can cause genetic changes within somatic cells, including hepatocytes and blood cells, as demonstrated by increased chromosomal breakage, sister chromatid exchange and decreased mitotic index (22,23). The HBV genome can integrate into the host genome; these non-specific integrations exist within different regions, leading to chromosomal instability (23).…”
Section: Discussionmentioning
confidence: 99%